Formulation of Business Development Strategies to Achieve Competitive Advantage - Khanza, Adillah Dhianida; Fakhri, Erie Awalil (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to develop a business development strategy for Candyco Handmade Crochet to address challenges related to marketing limitations, production management, and market competition, while improving competitiveness and business sustainability in the handmade crochet sector. Design/Methodology/Approach – This study employs a qualitative research approach. Data were analyzed to identify business challenges and formulate a comprehensive market development strategy focusing on innovative marketing strategies, production management improvement, and brand differentiation. Findings – The results indicate that the proposed strategies can increase Candyco Handmade Crochet’s opportunities to expand market reach, achieve revenue targets, and improve competitiveness. The strategies include implementing live shopping as an innovative marketing approach, optimizing production management to prevent stock imbalances, and strengthening brand differentiation to compete with similar businesses. Originality/Value This study offers value by presenting an integrated market development strategy tailored to a handmade creative business, combining innovative live-shopping marketing, structured production management, and clear brand differentiation. The proposed SOP and strategic framework provide practical, replicable guidance for Candyco and other creative SMEs seeking to strengthen their market position and pursue long-term growth.